Passenger cars carbone dioxide emission legislative regulation and tax application in the European Union. - Narogs, Niks (Riga Graduate School of Law, 2021)
Global warming has become in the past few years one of the main concerns for the countries, which has led to the goal to reduce targets of emissions on the national, supranational, and international levels. The transportation industry is one of the main sectors that are polluting the atmosphere with greenhouse gases, including Carbone Dioxide. The bachelor thesis purpose is to verify how the international level legislation is regulating the Carbone Dioxide emissions standards for the passenger cars, with the application on the European Unions as a supranational legislator. Moreover, to justify the European Unions’ correlation for the Member States of the Union tax rate passenger car laws and the possible gaps of that relation. In the result of the thesis, there was found the currently strong European Union’s Regulation (EU) 2019/631 focusing on the newly produced passenger cars emitted Carbone Dioxide emissions, there is not direct relation and regulation on the legal grounds for the EU and national level, there is difference between the country legislations towards the tax rates imposed on the vehicles.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Environmental law; Carbone dioxide emissions